VD_FINDINFO HC / 2011 / 540 vom 15. September 2011 - VD Tribunal cantonal (2011)
GROSSESSE, RÉSILIATION, JUSTE MOTIF, CONTRAT DE TRAVAIL | 4 CC, 336c al. 1 let. c CO, 336c al. 2 CO, 337 al. 1 CO, 337 al. 2 CO